Explaining consumer engagement in e-sports - demographic and social considerations = Badanie zaangażowania konsumentów w e-sport - uwarunkowania demograficzne i społeczne - Kordyaka, Bastian; Kruse, Björn; Niehaves, Björn (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Based on assumptions from marketing and social psychology, this paper aims at obtaining a better understanding on how to engage consumers in e-Sports using brand identification and demographic dispositions (i.e., age, education) as antecedent variables. We collected a sample of 216 League of Legends consumers, via the crowdsourcing marketplace Mechanical Turk to explain consumer engagement of e-Sports brands. Using a quasi-experimental approach and structural equation modelling, we show that brand identification affects consumer engagement in a positive manner. Our results indicate that age has a negative and education a positive influence on brand identification and consumer engagement.
Keywords: e-sports; Consumer Engagement; social identity; BrandManagement; age; education; e-sport; zaangażowanie konsumentów; tożsamość społeczna; zarządzanie marką; wiek; edukacja